Impact of Covid-19 on the Visit of Pediatric Patients with Injuries to the Emergency Department in Korea - Arum Choi; Woori Bae; Kyunghoon Kim; Sukil Kim (MDPI AG, 2021)
The total number of pediatric emergency department (PED) visitors has decreased worldwide since the coronavirus disease (COVID-19) outbreak. We hypothesized that this might also affect the number of PED visits due to injuries. Therefore, we investigated these changes in PED visits after the COVID-19 outbreak through a long-term multicenter observational study. We assessed the changes in the proportion of injured pediatric patients' weekly visits and the trend in the rate changes since the COVID-19 epidemic began by segmented regression analysis. We also evaluated the weekly change in the distribution of detailed diagnostic codes among pediatric patients with injuries before and after the COVID-19 pandemic. The proportion of injury-related PED visits increased when COVID-19 was first confirmed in Korea. After the COVID-19 epidemic, the proportion of foreign body ingestions and fracture patients among all pediatric patients with injuries increased significantly every week. The changes in the proportion of injured pediatric patients after the COVID-19 outbreak may have been the result of social distancing to prevent the spread of the virus. The risk of pediatric infections decreased but the risk of injury remained. Therefore, parents should take precautions to prevent infectious diseases and be careful to prevent children's injuries at home.